HUBUNGAN HIPERURISEMIA DAN FRACTION URIC ACID CLEARANCE DI DESA TENGANAN PEGRINGSINGAN KARANGASEM BALI - Kurniari, Pande Ketut; Kambayana, Gde; Raka Putra, Tjokorda (journal of internal medicine, 2011)
Hyperuricemia is a condition of high consentration of uric acid in the blood. In most epidemiology study hyperuricemiais defined as level uric acid more than 7.0 mg/dl in men and more than 6.0 mg/dl in women. Hyperuricemia can be caused byseveral factors. Regarding the etiology hyperuricemia can be classified as primary, secondary and idiopathic hyperuricemia.Primary hyperuricemia related to genetic factor while secondary hyperuricemia caused by condition or other factors besidesgenetic factor such as high purin consumption, chronic kidney disease, certain drugs, alcohol and hypertension. Hyperuricemiacan be caused by inceased of uric acid metabolism (overproduction), decreased of urine uric acid excretion (underexcretion),or mix of both. Fraction Uric Acid Clearance (FUAC) is one of the method used to differentiate either hyperuricemia caused byoverproduction or underexcretion. The aim of this studi is to determine the prevalence of hyperuricemia, means value of FUACand association between hyperuricemia and FUAC in Tenganan Pegringsingan Karangasem region Bali.A cross sectional analytic study was conducted on Balinesse in Tenganan Pegringsingan Karangasem region. Samplestudy was Balinese at age of 13 years old or above, agree to participate by informed consent. Descriptive statistic analysis onnumeric data presented as mean mean ± SD, nominal and ordinal data in proportion. Pearson?s correlation method is used incomparing the correlation between hyperuricemia and FUAC. Of 100 eligible samples, mean age was 37.20 ± 13.59 y.o, 51(51%) men and 49 (49%) women. Youngest age was 13 y.o and oldest was 69 y.o. Mean of blood uric acid level was 5.69 ± 1.43mg/dl. Prevalence of hyperuricemia on this study was 28%, 21% men and 7% women. Means value of FUAC is 6.41 + 1.99%;6.94 + 2.01% in normal uric acid level and 5.04 ± 1.1% in hyperuricemia. There is close correlation between hyperuricemia andFUAC (r = 0.43; p = 0.00)